PENGARUH BRAND CREDIBILITY MASKAPAI PENERBANGAN TERHADAP PURCHASE INTENTION KONSUMEN DI SURABAYA - Slamet Riyadi; Dudi Anandya; Indarini Indarini (Perpustakaan Universitas Surabaya, 2018)
The purpose of this research is to understand and analyze the influence of airlines brand credibility toward consumer purchase intention in Surabaya. Data processing was conducted using SPSS 18 for Windows and Amos Graphic 21 for Windows. The sampling technique thatused is non-probability sampling with purposive sampling type. 150 respondents who qualify the specified characteristics of the population were the total of sample used in this research which distributed by offline quetionaire. The result of this research that there was a positive influence between brand credibility on decision convenience, a positive influence between decision convenience on purchase intention, a positive influence between brand credibility on affective commitment, a positive influence between affective commitment on purchase intention and a positive influence between brand credibility on purchase intention.